Doświadczenie moralne a wiara - WIERZBICKI, Alfred M. (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Tadeusz Styczeń’s personalist ethics, which refers to moral experience, remains open to the evidence provided by the Revelation. Moral experience may be interpreted both in the «language of values» and in the «language of duty.» While obeying the principle of accurate description of moral experience, Styczeń stresses the relation between the moral duty and the dignity of the person, and interprets this relation as an objective reason for the duty to affirm the person as a value in ifself. The autonomy of moral experience determines the autonomy of what is «due» in the moral sense, and thus ethics turns out to be a discipline which remains independent of metaphysics or religion. Moral duty, which is experientially acknowledged, demands a further metaphysical analysis. While Hume pointed that there exists an unbridgeable gulf between «is statements» to «ought statement,» Styczeń points to the actual experiential grasp of moral duty and even formulates the thesis that there is a necessary passage from «ought statements» to «is statements.» In his pursuit of the ontologically ultimate moral duty which simultaneously conforms to the evidence of human experience, the ethicist cannot fail do discover the Absolute as Person. The metaphysics pursued in the light of moral experience becomes then a metaphysics of gift. Within the evidence of human experience lies the fact of moral collapse of man. While attempting to explain the phenomenon which Ovid described by means of his famous adage: Video meliora proboque, deteriora sequor, ethics becomes a «philosophy of the Advent,» open to the saving interference of God in human history. The Christian vision of the misery and the glory of man confirms the evidence provided by moral experience; moreover, it sheds new light on it. An adequate solution of the problem of man demands an adequate answer to the question of who man is, while this answer is to be sought by way of synthesis of reason and faith. Translated by Dorota Chabrajska